Feminism and Gender Equality in Bali: A Cultural Perspective Through Simone de Beauvoir - Wardana, Danara Kanya Magali (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study explores the intersection of feminism and gender equality in Bali, analyzing how patriarchal norms, media portrayals, and religious customs marginalize Balinese women. Using Simone de Beauvoir’s concept of the “Other,” it examines why feminism faces resistance despite growing gender equality awareness. Through surveys and interviews with Balinese women aged 11–20, the findings reveal that many support gender equality but hesitate to identify as feminists due to cultural misconceptions and Western associations. The research highlights the need for educational initiatives and community discussions to integrate feminism into Balinese traditions, showing that culturally adapted advocacy is more effective than universalist approaches. It underscores the importance of feminist education, local leadership engagement, and promoting women’s roles within traditional structures, demonstrating that feminism and Balinese traditions can coexist without disrupting social harmony. Future research should explore generational shifts, digital media’s role in shaping perceptions, and comparative studies in other traditional societies to further bridge feminism and cultural values.